2022
DOI: 10.1097/aog.0000000000004734
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Remdesivir and Intensive Care Unit Admission in Hospitalized Pregnant Individuals With Coronavirus Disease 2019 (COVID-19)

Abstract: Remdesivir has been shown to shorten the time to recovery in hospitalized patients with coronavirus disease 2019 . Data on its use in pregnancy are limited. In this single-center retrospective cohort study, our objective was to determine whether early remdesivir use in pregnant individuals is associated with decreased risk of admission to the intensive care unit (ICU). Forty-one pregnant patients were included in this study, and outcomes were compared between those who received remdesivir less than 7 days (ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Cesarean delivery rate was higher among women who received remdesivir postpartum vs. during pregnancy [ 8 ]. Early RDV administration was associated with improved clinical outcomes, including lower rates of ICU admission and decreased progression to critical disease in pregnant individuals hospitalized with COVID-19 [ 11 ], in line with reports in the general population [ 12 ]. Similarly, early RDV administration was associated with improved pregnancy outcomes, including numerically lower rates of preterm delivery and maternal death from COVID-19 in pregnant individuals hospitalized with COVID-19 [ 11 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cesarean delivery rate was higher among women who received remdesivir postpartum vs. during pregnancy [ 8 ]. Early RDV administration was associated with improved clinical outcomes, including lower rates of ICU admission and decreased progression to critical disease in pregnant individuals hospitalized with COVID-19 [ 11 ], in line with reports in the general population [ 12 ]. Similarly, early RDV administration was associated with improved pregnancy outcomes, including numerically lower rates of preterm delivery and maternal death from COVID-19 in pregnant individuals hospitalized with COVID-19 [ 11 ].…”
Section: Discussionsupporting
confidence: 77%
“…Early RDV administration was associated with improved clinical outcomes, including lower rates of ICU admission and decreased progression to critical disease in pregnant individuals hospitalized with COVID-19 [ 11 ], in line with reports in the general population [ 12 ]. Similarly, early RDV administration was associated with improved pregnancy outcomes, including numerically lower rates of preterm delivery and maternal death from COVID-19 in pregnant individuals hospitalized with COVID-19 [ 11 ]. Data from 35 hospitalized pregnant women during the period from 1 April to 31 December 2020 were retrospectively analyzed, and the results showed that all 17 women who initiated RDV within 48 h from admission presented prompt improvement and recovered by day 7 [ 13 ].…”
Section: Discussionsupporting
confidence: 77%
“…Remdesivir use in hospitalized pregnant women was well tolerated, without an increase in adverse maternal or neonatal outcomes [ 64 ]. Early administration of remdesivir within 7 days of symptom onset was associated with lower intensive care admission, progression to severe disease and shorter length of hospital stay [ 65 ].…”
Section: Special Populationsmentioning
confidence: 99%
“…This left health care providers in the position of counseling and caring for pregnant patients with minimal data. After many pregnant individuals were treated and retrospective data were analyzed, similar efficacy and adverse event profiles between pregnant and nonpregnant individuals for common therapies, such as remdesivir and monoclonal antibodies, were observed, based on real‐world data 26,27 . Of note, the RECOVERY trial, conducted in the United Kingdom, did include pregnant individuals.…”
Section: Policy Changes and Current State Of Affairsmentioning
confidence: 99%
“…After many pregnant individuals were treated and retrospective data were analyzed, similar efficacy and adverse event profiles between pregnant and nonpregnant individuals for common therapies, such as remdesivir and monoclonal antibodies, were observed, based on realworld data. 26,27 Of note, the RECOVERY trial, conducted in the United Kingdom, did include pregnant individuals. Data from that trial, which demonstrated that dexamethasone use was associated with lower 28day mortality among those with an oxygen requirement, enabled obstetricians in the United States to introduce an evidence-based intervention into COVID-19 management protocols in pregnancy.…”
Section: Coronavirus Disease 2019mentioning
confidence: 99%